Penegakan Hukum Lingkungan Menurut UUPLH - Zairin Harahap (Fakultas Hukum Universitas Islam Indonesia, 2004)
The enforcement o fenviroment law according to the Enviromentalt management Law can be implemented both in a preventive and repressive manner. The enforcement of enviromental law in a preventive manneraims to directly prevent the occurrence of enviromental damage or pollution. The legal instrument used is administrative law, in the format an obligation imposed upon each person who intends toruna business, to first obtain an environmental impact assessment of the proposed business. The represiveenforcement of law alms toreduce and a bateexisting environmentald a mage of pollution by using administrative law civil law and criminal law